Nanotechnology Applications towards Sustainable Road Surface Maintenance and Effective Asset Protection, Generating Rapid Employment Opportunities in a Post COVID-19 Era - Gerrit J. Jordaan; Wynand J. vdM. Steyn (Applied Sciences, 2022)
The developing world has been faced with high rates of unemployment, exacerbated by extended enforced lockdowns due to the pandemic. Pressure is mounting for drastic intervention to accelerate economic growth and to provide employment opportunities. Most of these countries are faced with inadequate road transport facilities in support of economic growth. The construction of high-order roads in support of economic growth requires high degrees of compliance with limited opportunities for increased labour content. However, many of the existing surfaced roads are notoriously lacking periodic preventative maintenance operations needed to preserve the integrity of road surfaces to protect pavement structures against water ingress and resultant rapid deterioration. This article demonstrates the ability of available, proven nanotechnologies to restore the water-resistant properties of already compromised road surfacings. It is shown that traditionally used road products can substantially be improved (in terms of strength properties and resistance to environmental factors) through the addition of applicable nanotechnology modifiers. These modified products can be applied at ambient temperatures, ideally suited for labour intensive applications as demonstrated, showing several examples of actual applications. A combination of modified existing technologies is recommended to partially restore severely compromised road surfacings, especially applicable to secondary and tertiary urban road networks. The implementation of the recommended restoration programmes can go a long way towards road asset preservation, while simultaneously addressing the urgent need for rapid employment generation.